2007
DOI: 10.1007/s10554-007-9277-x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital coronary artery fistulas in adults: concomitant pathologies and treatment

Abstract: Coronary artery fistulas are incidentally diagnosed during coronary artery angiographies in adults and should be closed to prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 8 publications
1
40
1
Order By: Relevance
“…Elective ligation in childhood has been recommended because of increasing incidence of late symptoms and complications in older patients. 1,2 Despite passage of 50 and 25 years from first reports of successful surgical ligation 3 and transcatheter closure (TCC), 4,5 respectively, of coronary fistulae, few descriptions exist of intermediate or long-term outcome from such interventions.…”
mentioning
confidence: 99%
“…Elective ligation in childhood has been recommended because of increasing incidence of late symptoms and complications in older patients. 1,2 Despite passage of 50 and 25 years from first reports of successful surgical ligation 3 and transcatheter closure (TCC), 4,5 respectively, of coronary fistulae, few descriptions exist of intermediate or long-term outcome from such interventions.…”
mentioning
confidence: 99%
“…Because of the low prevalence of coronary artery fistulas, the optimal management remains unclear and there are no established therapeutic guidelines. Treatment with percutaneous intervention or surgery is recommended for patients with symptoms such as chest pain and dyspnea (4,10,15,(18)(19)(20) and to prevent the development of heart failure (4-7), myocardial ischemia (4, 6, 8-10), endocarditis (11) or rupture of aneurysmal vessels (12)(13)(14). Cebi et al indicated that symptomatic coronary artery fistulas should be closed irrespective of the size of the left-to-right shunt (4).…”
Section: Discussionmentioning
confidence: 99%
“…A coronary artery fistula is a relatively rare anomaly, observed as an incidental finding on 0.05-0.2% of coronary angiograms (1)(2)(3)(4). Coronary artery fistulas can result in heart failure (4-7), myocardial ischemia (4,6,(8)(9)(10), endocarditis (11) and rupture of aneurysmal vessels (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations